Analisis Financial Distress dengan Metode Z-Score Altman pada Perusahaan Sektor Teknologi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Rian Kurniawan (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Technology sector companies are companies that have a major impact on the Indonesian economy because they are the foundation during the Covid-19 pandemic. However, the conditions of Covid-19 and the turmoil of the global economic recession have caused many technology sector companies to experience financial difficulties and even lose investors. The purpose of this study is to determine the level of financial distress, the best companies, and overall faced by technology sector companies during the 2019-2022 period using the Modified Altman Z-Score method for prediction analysis. This research is a non-statistical quantitative method research. The population used was 21 companies, with purposive sampling technique and the samples taken were 4 technology sector companies listed on the Indonesia Stock Exchange during the 2019-2022 period. The indicator variables used in this study are the ratio of Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), Earning Before Interest and Tax to Total Assets (X3), and Book Value of Equity to Book Value of Total Debt (X4). The results of this study found that in 2019 there was 1 company in the gray area category. In 2020-2022 all companies were in good health, and PT Hensel Davest Indonesia Tbk (HDIT) became the best company. The conditions of the Covid-19 pandemic and the economic turmoil of the global recession that occurred from 2019-2022 had no impact on the level of financial distress in technology sector companies.